Taxonomy of the Indian Endemic Herb-Solanum purpureilineatum Sabnis & Bhatt (Solanaceae) - Singh, R. Kr.; Garg, Arti (Indian Forester, 2018)
The little known endemic species Solanum purpureilineatum Sabnis and Bhatt is often considered conspecific with S. nigrum L. Cultivation experiments, critical studies of herbarium specimens and live specimens confirmed that both species are distinct, hence S. purpureilineatum Sabnis and Bhatt is reinstated here. The name S. purpureilineatum Sabnis and Bhatt is lectotypified here because in the protologue two specimens are designated as holotype instead of one and a detailed taxonomic account, coloured photographs and distribution are provided.